FACTORS INFLUENCING THE DECISION OF MUSLIM GENERATION Z TO USE TIKTOK SHOP FROM A MASLAHAH PERSPECTIVE - Jumarni (Jurnal Ilmiah Al-Tsarwah, 2025)
The rapid growth of social commerce through TikTok Shop has transformed consumption behavior among young generations, including Muslim Generation Z. This phenomenon raises questions regarding the factors influencing decisions to use TikTok Shop, particularly when examined through the lens of planned behavior and Islamic economic values. This study aims to analyze the effects of attitude, subjective norms, perceived behavioral control, and concern for maslahah on TikTok Shop usage decisions among Muslim Generation Z, with intention serving as a mediating variable. Employing a quantitative approach, this study collected survey data from 155 students of the State Islamic Institute (IAIN) Bone who had experience using TikTok Shop. Data were analyzed using Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach. The results indicate that attitude has a positive and significant effect on intention, and intention significantly influences TikTok Shop usage decisions. In contrast, subjective norms, perceived behavioral control, and concern for maslahah do not have a significant effect on intention. Intention is found to mediate the relationship between attitude and usage decisions. These findings confirm the relevance of the Theory of Planned Behavior in explaining digital consumption behavior among Muslim Generation Z, while also suggesting that maslahah values have not yet been strongly internalized in social commerce practices. This study contributes to the literature on digital consumer behavior from an Islamic economics perspective and offers practical implications for digital platform managers and business practitioners